PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA DI DESA MOJO KECAMATAN ANDONG KABUPATEN BOYOLALI - Joko Pramono & Jana Harjanta, Toni Ari Wibowo (Transformasi, 2014)
The result of this study is that community participation in rural development in the village of Mojo is still influenced by a variety of things such as employment issues, economic inequality, and still dependent society with government, village government, and central government. Meanwhile, to reduce unemployment participation of the community is also not involved because of the lack of community involvement in providing training or skills to other communities. Keywords : participation; community; development